Vestibular Contributions to Health and Disease - Richard Lewis; Jose Antonio Lopez-Escamez; Bernard Cohen (Frontiers Media SA, 2018)
This eBook reviews recent developments in vestibular physiology and pathophysiology and covers a range of topics, including diagnostic tests, treatment approaches, central and peripheral vestibular mechanisms, and vestibulo-automonic interactions.
English
Keywords: autonomic; pathophysiology; physiology; eye movements; vestibular; perception